Cholesterol crystal as a new feature of coronary vulnerable plaques: An optical coherence tomography study. Issue 1 (January 2017) - Nishimura, Satoshi; Ehara, Shoichi; Hasegawa, Takao; Matsumoto, Kenji; Yoshikawa, Junichi; Shimada, Kenei
Abstract: Background: Previous pathohistological studies demonstrated that cholesterol crystals (CCs) are frequently observed in atherosclerotic plaques, and are usually present abundantly in vulnerable plaques. However, the role of CCs in plaque destabilization, as well as their origin and composition, is unknown. Optical coherence tomography (OCT) imaging system is a high-resolution imaging device, which allows the in vivo identification of CCs accumulating within atherosclerotic plaques. The aim of this study was to investigate the relationship between the presence of CCs, other plaque morphologies assessed by OCT, and patients' clinical characteristics including acute coronary syndrome (ACS). Methods and results: Preinterventional OCT images of 173 patients with either ACS or stable angina pectoris were studied. Of 173 lesions in the patients, 66 (38%) had CCs within the culprit lesion segment and 107 (62%) had non-CC lesions. Multivariate analysis revealed that low high-density lipoprotein cholesterol levels, diabetes mellitus, the presence of plaque rupture, intimal vasculature, and thrombus were independent factors associated with CCs. Moreover, the frequency of CCs increased in proportion to the accumulation of the number of components of their vulnerable plaque features within the culprit lesion segment. Compared with the plaques without thrombus, CCs were present at shallower locations in those with thrombus. Conclusions: This study demonstrates the potential correlation between the clinical metabolic disorder and vulnerable morphological features of culprit lesions to the presence of CCs in patients with stable and unstable coronary syndromes. These observations of CCs by using in vivo plaque imaging could provide incremental value to OCT evaluation of atherosclerotic plaques.